Kriminalisasi Buruh Perempuan Dalam Memperjuangkan Haknya Sebagai Pekerja - Gilang Billyone Ramadhan; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. challenges faced by female workers in fighting for their labor rights in several countries, including Indonesia. Social, cultural, economic, and legal factors are the main barriers for female workers, with criminalization being one of the significant obstacles. Legal practices such as criminal threats, criminalization, and Strategic Lawsuits Against Public Participation (SLAPP) worsen their situation. In addition, gender discrimination in the workplace, often driven by patriarchal stereotypes, makes female workers more vulnerable to exploitation and rights violations, and exacerbates inequalities in wages, job opportunities, and protection. Criminalization also has a negative impact on their social, economic, and mental well-being, increasing social isolation, stigma, and economic difficulties. This study recommends the need for policy changes that are more supportive of women, the elimination of gender stereotypes, and legal reforms to protect female workers from discrimination and criminalization, as well as the creation of a fairer and more inclusive labor system